The effect of portacaval anastomosis on oral carbohydrate tolerance and on plasma insulin levels. Issue 1 (January 1972) - Holdsworth, C. D.; Nye, Lynne; King, Elizabeth
Abstract : In patients with portal hypertension, plasma insulin levels were raised both fasting and after oral glucose or intravenous tolbutamide. This supports previous suggestions that resistance to endogenous insulin plays a major role in producing the impaired glucose tolerance found in chronic hepatic dysfunction. The operation of portacaval anastomosis was followed by impaired oral fructose tolerance, but did not significantly change oral glucose tolerance. Plasma insulin levels were unchanged by the operation, either fasting or following the stimulus of an oral glucose load or intravenous tolbutamide. The insulin response after operation was only higher after intensive pancreatic β cell stimulation by a combination of glucose, tolbutamide, and glucagon. These results indicate that, in patients with hepatic dysfunction, little insulin is being removed by the liver from the portal blood except when the insulin secretory rate is unusually high.